Critical success factor for partnership in low-cost apartments project: Indonesia perspective. (4th May 2018) - Rachmawati, Farida; Soemitro, Ria Asih Aryani; Adi, Tri Joko Wahyu; Susilawati, Connie
Abstract: Accessibility to low-cost apartments for migrant workers is a key housing problem in East Java Province, particularly in Surabaya, which results in the housing backlog. Indonesian Ministry government has constructed low-cost apartments in local Government's asset land and has initiated the housing finance policy to support mortgage loan. However, the existing low-cost apartments are located far from employment centre and there is lack of private sector involvement. As a form of support to the Government's programme for providing low-cost apartments, the private sector, such as industrial estate, is expected to contribute towards providing such apartments to industrial employees especially migrant workers. A survey of key stakeholders conducted to investigate the specific critical success factors that lead to successful partnerships in low-cost apartment projects. The factor analysis yielded five specific inter-related group factors, namely housing finance policy, government support, stakeholder's commitment, procurement and community support. Furthermore, the study suggests some recommendations in relation to land availability and adequate housing policy to support the implementation in the future.